The relationships between marketing variables and their effects on each other - Imani Khoshkhoo, Mohammad Hossein; Yousefi, Homayoun (Opción, 2019)
The objective of this study is to evaluate the relationships between the marketing variables and their effects on each other. This study has been conducted by the use of the descriptive-survey method, and it is an applied study. The results show that the studied elements (physical proofs, mental images, expectations, perception, satisfaction, branding, packing, workplace, positioning, positioning the product, and loyalty) have positive and significant effects on each other. In conclusion, all of the concepts defined in this article have strong conceptual relationships with each other and have decisive roles in the customers’ satisfaction with the destination.